Bio-psycho-social management model: Role of liaison psychiatry - Ahmed, Syed Kamaluddin (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i1.3841 Journal of Chittagong Medical College Teachers' Association 2008: 19(1):1-3